Relationship between hemineglect and pain: a systematic review and meta-analysis of randomized controlled trials (2021)
Objective: To identify the relationship between hemineglect and pain. Methods: We conducted a systematic review with meta-analysis, examining the relationship between hemineglect and pain. The PRISMA criteria and the Covidence platform were used to select articles and extract data. Methodological quality was evaluated, a comparison was made using pain as an outcome measure, assessed with the visual analog scale (VAS). Results: Out of a total of 340 studies, 4 were selected, 2 of which made it possible to unify pain measured through VAS; the effects were summarized using standardized mean differences (SMD), yielding -0.65, with values of [-1.02, -0.29], with statistical significance. Conclusions: There is moderate evidence of the relationship between negligence and pain. Despite the fact that from the clinical care processes it is presented regularly, and even the little scientific information available, it was established that there are specific pathologies that carry negligence and pain.